2016
DOI: 10.1016/j.ymeth.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the AAVS1 locus for consistent and scalable transgene expression in human iPSCs and their differentiated derivatives

Abstract: The potential use of induced pluripotent stem cells (iPSCs) in personalized regenerative medicine applications may be augmented by transgenics, including the expression of constitutive cell labels, differentiation reporters, or modulators of disease phenotypes. Thus, there is precedence for reproducible transgene expression amongst iPSC sub-clones with isogenic or diverse genetic backgrounds. Using virus or transposon vectors, transgene integration sites and copy numbers are difficult to control, and nearly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
170
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(192 citation statements)
references
References 44 publications
0
170
0
Order By: Relevance
“…This allowed us to confirm GFP-tag incorporation without large insertions or deletions (Figure 2A, middle panel, step 2) (Jasin and Rothstein, 2013; Oceguera-Yanez et al. , 2016).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This allowed us to confirm GFP-tag incorporation without large insertions or deletions (Figure 2A, middle panel, step 2) (Jasin and Rothstein, 2013; Oceguera-Yanez et al. , 2016).…”
Section: Resultsmentioning
confidence: 78%
“…Donor plasmid integration was the most common category of imprecise editing, affecting 45% of all clones (Figure 2F). Our data suggest that this frequently occurs at the edited locus as a faulty by-product of the editing process and that screening by junctional PCR alone, without a method to directly detect the plasmid backbone, leads to misidentification of clones with imprecise editing, despite appropriate localization of the tagged protein resulting from the edit (Figure 2F and Supplemental Figure S4; Jasin and Rothstein, 2013; Oceguera-Yanez et al. , 2016).…”
Section: Resultsmentioning
confidence: 81%
“…11 Genes introduced into the AAVS1 site in human PSCs showed stable expression after in vitro and in vivo differentiation. 5,[12][13][14][15] The clustered regularly interspaced short palindromic www.moleculartherapy.org repeats (CRISPR)/CRISPR-associated nuclease 9 (Cas9) system is a highly efficient RNA-guided DNA nuclease system modified from an adaptive immune system of bacteria and archaea to allow sequence-specific genome editing in human cells. [16][17][18] Recent reports have indicated that the CRISPR/Cas9 system can be used for genetic modification in NHPs; however, this approach has not yet been applied to insert genes of interest into the AAVS1 safe harbor in NHP PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…To further test our miR-Cas9 switch in different cell types, we next chose a human iPS cell line (201B7) that contains a single copy of the EGFP gene at the AAVS1 locus, which is often considered a safe-harbor for transgene targeting (hiPSC-EGFP) (19). We used the miR-302-Cas9 switch to selectively repress Cas9 activity in hiPSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The heterozygously targeted AAVS1-CAG::GFP human iPSCs 317-12 line (hiPSC-EGFP) (19) was maintained in StemFit (Ajinomoto) on laminin-511 E8 (iMatrix-511, nippi). HeLa-EGFP cells were cultured in DMEM High Glucose (nacalai tesque) supplemented with 10% FBS (JBS) and Hygromycin B (50 μg/ml).…”
Section: Methodsmentioning
confidence: 99%